What explains citizens' valuations of and attitudes towards agricultural biodiversity? Results of an exploratory survey of Dutch students. (1st November 2019) - Runhaar, Hens; Buijs, Arjen; Runhaar, Piety
Highlights: Citizens' valuations of agricultural biodiversity are poorly understood. We explore how valuations, attitudes, underlying and mediating factors are related. Students appreciate intrinsic and aesthetic values of agricultural biodiversity. Knowledge provision is needed to enhance the valuation of agricultural biodiversity. Abstract: Citizens' valuation of agrobiodiversity is important for retaining political interest in the subject, for legitimising agri-environment schemes and other conservation initiatives and for their own willingness to contribute to agrobiodiversity conservation. Still little is known about whether and how citizens value agrobiodiversity, how these valuations can be explained and what they imply for citizens' preparedness to contribute to the enhancement of agrobiodiversity. We report on the findings of an exploratory survey aimed at uncovering the above mechanisms among a specific subgroup of Dutch citizens: students. We conclude that (a) students appreciate the intrinsic and aesthetic values of agrobiodiversity to some extent, but not its instrumental value; (b) valuations correlate with students' fundamental values; (c) students' attitudes correlate strongly to how they value agrobiodiversity. We recommend follow-up research among a more representative sample of Dutch citizens, with the aims to further test the mechanisms, assess valuations of agrobiodiversity by Dutch citizens in general and explore whether and how these valuations can be enhanced by the provision of information about the intrinsic and aesthetic values of agrobiodiversity.